2019
DOI: 10.1002/14651858.cd012379.pub2
|View full text |Cite
|
Sign up to set email alerts
|

eHealth interventions for people with chronic kidney disease

Abstract: 8. Art. No.: CD012379. Cochrane Reviews are regularly updated as new evidence emerges and in response to comments and criticisms, and the Cochrane Database of Systematic Reviews should be consulted for the most recent version of the Review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 110 publications
3
62
0
1
Order By: Relevance
“…With the rapid growth and momentum of eHealth, one of the most pressing concerns is that its efficacy in kidney care remains unclear. A 2019 Cochrane review concluded that overall, the evidence for eHealth interventions is of low quality and insufficient to guide clinical practice in kidney disease 6 . Moreover, a randomized trial that included 601 patients with CKD found that an eHealth intervention that used home monitoring devices to obtain biometric data (for example, blood pressure and weight) and deliver multidisciplinary care did not reduce mortality, hospitalization rates, emergency department visits or nursing home admissions when compared with usual care 4 .…”
Section: Efficacy Of Ehealth Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the rapid growth and momentum of eHealth, one of the most pressing concerns is that its efficacy in kidney care remains unclear. A 2019 Cochrane review concluded that overall, the evidence for eHealth interventions is of low quality and insufficient to guide clinical practice in kidney disease 6 . Moreover, a randomized trial that included 601 patients with CKD found that an eHealth intervention that used home monitoring devices to obtain biometric data (for example, blood pressure and weight) and deliver multidisciplinary care did not reduce mortality, hospitalization rates, emergency department visits or nursing home admissions when compared with usual care 4 .…”
Section: Efficacy Of Ehealth Interventionsmentioning
confidence: 99%
“…On average, participants took 14.9 blood pressure measurements per month and used the educational modules on 5.8 days per month 4 . Multiple other studies have reported high participant satisfaction with kidney eHealth interventions for a variety of reasons, including ease of use, low burden and increased frequency and quality of interactions with health-care staff 6 .…”
Section: Efficacy Of Ehealth Interventionsmentioning
confidence: 99%
“…eHealth refers to 'health services and information delivered or enhanced through the internet and related technologies', 14 which includes internet and computer, mobile phone (the use of text messaging and applications on mobile phones), telehealth, electronic monitors and wireless and Bluetooth enabled devices. 15 eHealth interventions have become increasingly popular due to making treatments more accessible and affordable. 16 17 They provide benefits for patients with an inconvenient location or commute and unavailable or inflexible times, and patients may receive the required information in a cost-effective way.…”
Section: Open Accessmentioning
confidence: 99%
“…There are examples of eHealth in musculoskeletal physiotherapy and medical specialties, such as ophthalmology, dermatology, radiology, urology, physical medicine and rehabilitation, and orthopaedics. [4][5][6][7][8][9][10][11][12][13][14] Sport and exercise medicine (SEM) physicians can learn from these but should also develop and implement their own guiding principles.…”
Section: Introductionmentioning
confidence: 99%